Obstacles to The Implementation of Regional Regulation of West Nusa Tenggara Province Number 2 of 2016 concerning Halal Tourism in Restaurants in Mataram City - Herlina (Faculty of Economics and Business, University of Mataram, 2023)
This study aims to identify the obstacles that exist in the halal certification process for restaurants in the city of Mataram. The method used is descriptive qualitative analysis to examine the hindrances in the halal certification process for restaurants as stipulated in the Regional Regulation of West Nusa Tenggara Province No. 2 of 2016 concerning halal tourism. The study was conducted at restaurants in the city of Mataram. Data collection techniques included direct observation using document instruments, interview guidelines, documentation, and literature studies. In conclusion, the implementation of West Nusa Tenggara Regional Regulation No. 2 of 2016 regarding Halal Tourism in the halal certification process for restaurants can be considered successful. However, there are several obstacles in the implementation process. These obstacles include communication issues between institutions due to the transition to an online-only application process for halal certification, a lack of government-led socialization efforts to inform business actors (due to budget constraints), and a shortage of adequately prepared human resources who understand the evolving system within the restaurant halal certification process.